COVID-19 - Myocarditis and return-to-play: Reflections and recommendations from a Canadian working group - McKinney, J.; Connell, K. A.; Dorian, P.; Fournier, A.; Goodman, J. M.; Grubic, N.; Isserow, S.; Moulson, N.; Philippon, F.; Pipe, A.; Poirier, P.; Taylor, T.; et al. (Canadian Journal of Cardiology, 2020)
The SARS-Coronavirus-2 (COVID-19) related pandemic has resulted in profound health, financial and societal impacts. Organized sporting events, from the recreational to Olympic levels, have been cancelled to both mitigate the spread of COVID-19 and protect athletes and highly active individuals from potential acute and long-term infection associated harms. COVID-19 infection has been associated with increased cardiac morbidity and mortality. Myocarditis and late gadolinium enhancement (LGE) as a result of COVID-19 infection has been confirmed. Correspondingly, myocarditis has been implicated in sudden cardiac death (SCD) of athletes. A pragmatic approach is required to guide those who care for athletes and highly active persons with COVID-19 infection. Members of the Community and Athletic Cardiovascular Health Network (CATCHNet) and writing group for the Canadian Cardiovascular Society/Canadian Heart Rhythm Society Joint Position Statement on the Cardiovascular Screening of Competitive Athletes recommend that highly active persons with suspected or confirmed COVID-19 infection refrain from exercise for 7 days after resolution of viral symptoms before gradual return to exercise. We do not recommend routine troponin testing, resting 12-lead electrocardiogram (ECG), echocardiography, or cardiac magnetic resonance imaging before return-to-play. However, medical assessment including history and physical examination with consideration of resting ECG and troponin can be considered in the athlete manifesting new active cardiac symptoms or a marked reduction in fitness. If concerning abnormalities on the initial medical assessment are encountered then referral to a cardiologist who cares for athletes is recommended.